# Pre-Algebra

posted by .

13 - t = -t + 7
(13 - t) - 13 = (-t +7) -13
-t = -t - 6
-t + t = (-t - 6) + t
0 = -6

This makes no sense to me..
What is the answer to the problem
13 - t = -t + 7

• Pre-Algebra -

it cannot be solved, you did it right. These types of equations are called no solution.

• Pre-Algebra -

um.. whats the question??

• Pre-Algebra -

What is the answer to the problem
13 - t = -t + 7

• Pre-Algebra -

-t = -t -6
0=-6
Thats the answer and you put no answer. That's just how some are.

• Pre-Algebra -

i was repeating the question; i'm not the op.

• Pre-Algebra -

Thank You all! I was trying to help my daughter and was all confused.

## Similar Questions

1. ### math

If Stephanie is scheduledto begin practiceat 12:30p.m., what is the latest time in which she could start getting ready to leave?
2. ### algbra

heyya Your equation makes no sense. Your equation makes no sense. 4x = y > 6 4x = y > 6 does it make since if you put a line under >. Because that is the question I am suppose to figure out.
3. ### ??

2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = a?
4. ### Algebra

Great Bob, now it makes sense!
5. ### education

I'm doing a power point on pre-k classroom. I need help finding a classroom arragment picture. Like how the room needs to be set up before a pre-k room open. I hope this makes sense.
6. ### Algebra

f(g(x)) =. Does this make sense or not? A) This makes sense because f(x) = x^2 and g(x) = x + 4 so putting in x^2 for x into g gives us x^2 + 4. B) This does not make sense because the input would first go into g, giving x + 4. Then

Determine whether the following statement makes sense or does not make sense, and explain your reasoning (modified from true/false format of text): If f(x) = 3x, then f^-1(x) = 1/3x A) This makes sense because the inverse would divide …